Understanding Hadith on Moderation and Interfaith Relations Among Students of the Faculty of Ushuluddin and Islamic Studies at UIN Sumatra Utara. - Azri Fahyuzi; Munandar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explores the understanding of Ushuluddin students towards hadiths that emphasize the value of moderation in Islam and its impact on attitudes of tolerance between religious communities. Using a mixed methods approach, this study involved 15 students for in-depth interviews and 50 students as respondents for a quantitative survey. Qualitative data were analyzed thematically to understand students' perceptions regarding moderation, while quantitative data were analyzed using correlational statistics to test the relationship between understanding of hadith moderation and attitudes of tolerance. The results of the study indicate that understanding of hadith moderation plays a significant role in increasing attitudes of moderation and tolerance, and has the potential to prevent the development of extremism among students. Factors such as social environment, interactions with friends, and the role of lecturers contribute to strengthening the understanding of moderation on campus. This study makes an important contribution to Islamic education literature by showing that the integration of moderation values ​​into the curriculum can create a more inclusive and peaceful academic environment. Further research is needed to develop effective educational strategies in preventing radicalization through teaching moderation.